Low-Frequency and Random Telegraph Noise Performance of Ge-Based and III-V Devices on a Si Platform - Claeys, Cor; Agopian, Paula [UNESP]; Alian, AliRezza; Arimura, Hiroaki; Fangs, Wen; Martino, Joao; Mitard, Jerome; Neves, Felipe; Oliviera, Alberto; Simoen, Eddy; Jiang, Y. L.; Tang, T. A.; et al. (Ieee, 2016)
This review demonstrates the potential of low frequency noise diagnostics for the characterization of Ge-based and III-V technologies processed on a Si platform. The analysis of traps in both gate dielectrics and semiconductor films is illustrated for state-of-the-art devices.